ONE WORD, TWO LANGUAGES, TWO INTERPRETATIONS: THE POLISH-LITHUANIAN TREATY OF 1994 AND HOW IT WAS (MIS)UNDERSTOOD - WALKOWIAK, Justyna (Comparative Legilinguistics, 2014)
The article studies the impact of the differences in the meaning of the word brzmienie in the Treaty on Friendly Relations and Good Neighbourly Cooperation of the Republic of Lithuania and Republic of Poland of April 26, 1994. The Polish word in question is ambiguous and has two potential meanings, whereas its equivalent used in the Lithuanian language version is unequivocal. Interestingly, the treaty was prepared only in Polish and Lithuanian, without the mutually accepted English version. Therefore the two (published by government-endorsed periodicals) translations into English of the text of the treaty that exist – one made by Poles and one by Lithuanians – have only unofficial status. The difference between these two English translations highlights best the divergence in how the two contracting parties obviously perceive their rights and obligations as circumscribed by the treaty. This divergence has figured heavily on the attitude of the media, and in due course influenced the public opinion in both states.